Perbandingan Tingkat Bagi Hasil Simpanan Mudharabah dan Modal Sendiri Antar Bank Umum Syariah di Indonesia Periode 2012-2015 - Andre Kurniawan; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to know the return level which is given to capital stockholders and also customers or clients that use ‘aqd mudharabah between islamic banks. Return represents that a bank can manage its fund well by giving satisfying return to capital stockholders and customers or depositors. This research compares ROE and ROMD inter-islamic banks. This research uses quantitativ-comparative method and it uses six islamic banks, and then, the researcher did different test of ROE and ROMD to it. Different test of ROE uses Kruskal-Wallis and Mann-Whitney tests, while different test of ROMD uses ANOVA and LSD tests. The result of ROE different test shows that there is a significant difference between one islamic bank to the others in Indonesia. The result of ROMD different test shows that there is no a significant difference between one islamic bank to the others in Indonesia.